2021
DOI: 10.1039/d1nj02218k
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the hydroboration of α,β-unsaturated carbonyl compounds catalyzed by a metal-free complex and subsequent C–C coupling with acetonitrile

Abstract: Herein density functional theory (DFT) method was employed to explore the reaction mechanism of selective hydroboration of α,β-unsaturated carbonyl compounds catalyzed by the metal-free complex, 1,3,2-diazaphospholene (DAP). The whole reaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…The average entropy error ( S err ) of the bimolecular adduction process for the present boron-based systems ( S err = 23.9 cal/mol/K) is similar to that of the transition-metal systems studied by Sakaki et al ( S err = 23.0 cal/mol/K) . The SMD and PCM solvent models have no significant impact on the Whitesides’ method (see Tables S2 and S4), and this method has been extensively applied to other reaction systems. On the other hand, Martin’s method involves using high pressure ((PCM, P = 1354 atm) M06/TZVP//BP86/SVP) to simulate the condensed-phase situation, and the entropy error varies from 17.7 to 32.7 cal/mol/K, as shown in Table S5, distinguishing it from the Whitesides’ method. The average value of S err evaluated by using Martin’s method is 25.7 cal/mol/K, slightly larger than the Whitesides’ correction in reducing the overestimated entropy.…”
Section: Computational Detailssupporting
confidence: 69%
“…The average entropy error ( S err ) of the bimolecular adduction process for the present boron-based systems ( S err = 23.9 cal/mol/K) is similar to that of the transition-metal systems studied by Sakaki et al ( S err = 23.0 cal/mol/K) . The SMD and PCM solvent models have no significant impact on the Whitesides’ method (see Tables S2 and S4), and this method has been extensively applied to other reaction systems. On the other hand, Martin’s method involves using high pressure ((PCM, P = 1354 atm) M06/TZVP//BP86/SVP) to simulate the condensed-phase situation, and the entropy error varies from 17.7 to 32.7 cal/mol/K, as shown in Table S5, distinguishing it from the Whitesides’ method. The average value of S err evaluated by using Martin’s method is 25.7 cal/mol/K, slightly larger than the Whitesides’ correction in reducing the overestimated entropy.…”
Section: Computational Detailssupporting
confidence: 69%
“…Pu and Lei et al carried out theoretical calculations (using DFT method) to investigate further the exact mechanism of the selective hydroboration of α,β-unsaturated esters. [62] Santos et al reported a novel protocol for phophine catalyzed hydroboration of alkynoic esters and amides. [63] This highly chemoselective protocol exclusively provided the transhydroboration product (104) (Scheme 19a) catalyzed by nBu 3 P. The most plausible mechanism was proposed based on theoretical and experimental outcomes (Scheme 19b).…”
Section: Hydroboration Of Carboxylic Esters and Amidesmentioning
confidence: 99%
“…Pu and Lei et al. carried out theoretical calculations (using DFT method) to investigate further the exact mechanism of the selective hydroboration of α,β‐unsaturated esters [62] …”
Section: Metal‐free Catalytic Hydroborationmentioning
confidence: 99%